2018
DOI: 10.1002/lary.27781
|View full text |Cite
|
Sign up to set email alerts
|

Septal fractures predict poor outcomes after closed nasal reduction: Retrospective review and survey

Abstract: Objectives/Hypothesis To determine outcomes of patients with displaced nasal bone fractures after closed nasal reduction (CNR). Study Design Retrospective patient review. Methods Review of all patients presenting to the emergency department of a tertiary‐care, level 1 trauma hospital with a nasal bone fracture over a 2‐year period, followed by telephone survey after CNR. Results Six hundred seven patients presented to the emergency department in 2015 and 2016 with a diagnosis of nasal bone fracture. Of these, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
0
12
1
2
Order By: Relevance
“…Among the patients undergoing a septoplasty, there were more men and they were younger than patients undergoing a septoplasty + turbinoplasty and turbinoplasty alone. The predominance of men in septoplasty has been likened to more nasal trauma in this group related to sports activities, assault and motor vehicle accidents, among others [ 14 ]. Why isolated septal deviations underwent surgery at an earlier age is not clear, but it is important in the assessment, as surgery at a young age is associated with a risk of a poorer outcome [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients undergoing a septoplasty, there were more men and they were younger than patients undergoing a septoplasty + turbinoplasty and turbinoplasty alone. The predominance of men in septoplasty has been likened to more nasal trauma in this group related to sports activities, assault and motor vehicle accidents, among others [ 14 ]. Why isolated septal deviations underwent surgery at an earlier age is not clear, but it is important in the assessment, as surgery at a young age is associated with a risk of a poorer outcome [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who have missed the optimal time for the operation (within 2 weeks after trauma) [ 18 ], CR is complicated by the formation of the callus which affects the operation. A retrospective review of 607 patients with nasal fractures reported that although only 5% of patients were dissatisfied with CR, 35% had some degree of nasal obstruction and 9% had nasal deviation [ 5 ]. Studies noted that 11–50% of patients had persistent deformities after CR and needed subsequent septoplasty [ 6 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although CR is a simple, fast and economical method, the procedure is performed blindly and is mainly guided by the experience of the surgeon. The outcomes of CR vary widely throughout the literature with patient satisfaction rates being reported between 30% [3,4] and 95% [5]. Some studies reported revision surgery rates after CR were between 5.5% and 11% [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…No que se refere à eficácia de reduções fechadas de fraturas nasais, María Dalbosco et al (2017) descreveram que a realização desse tratamento sob anestesia local se mostrou eficiente na melhora da aeração nasal, bem como na melhora da estética, em comparação com o estado pré-operatório, de acordo com dados informados pelos pacientes. Além disso, um estudo realizado por Arnold et al (2019) relatou que mais de 90% dos pacientes que foram submetidos ao tratamento de fratura nasal por redução fechada e responderam ao questionário da pesquisa, sentiram-se satisfeitos com o procedimento.…”
Section: Categoria 01: Anestesia E Analgesia Em Reduções Fechadas De unclassified
“…Observou-se que a existência de fratura septal associada à fratura óssea nasal é um indicativo de piores resultados na redução fechada das fraturas nasais, principalmente no que se refere à respiração nasal (Arnold et al, 2019), satisfação do paciente (Jeon & Kim, 2018) e risco de desenvolvimento de sinéquia pós-operatória ( Kim et al, 2015).…”
Section: Categoria 03: Complicações E Deformidades Nasais Secundáriasunclassified